Acceptance of the Use of HIV Surveillance Data for Care Engagement: National and Local Community Perspectives. (1st May 2015) - Evans, David; Van Gorder, Dana; Morin, Stephen F.; Steward, Wayne T.; Gaffney, Stuart; Charlebois, Edwin D.
Abstract : Background: Use of surveillance data including laboratory results (e.g., CD4 and HIV RNA) by public health departments to facilitate linkage, retention, and reengagement of HIV-infected individuals in health care is on the rise. This is part of the goal of increasing the proportion of infected persons achieving virologic suppression. However, this use of surveillance data is not without controversy, particularly among some providers and people living with HIV. Methods: We conducted informal discussions with key stakeholders and a literature search and held a national think tank in November 2012, bringing together 31 representatives of the federal government, county and state officials, health care providers, and community-based organizations. A follow-up community consultation specific to San Francisco was held January 24, 2014, with 10 participants. Notes from these activities were used as data for this analysis. Results: The think tank identified 3 strategies using HIV surveillance data to aid in care engagement: (1) provider-mediated, where health department staff work with the provider of record on reengagement, (2) electronic linkages between surveillance databases and medical records databases, and (3) direct outreach, where trained health department staff reach out to persons out of care. Participants also developed recommendations for minimizing harm, guidance on meaningful stakeholder involvement, and a consensus statement in support of the use of HIV surveillance data in care engagement. Conclusions: Acceptance of the use of surveillance data for HIV care linkage, retention, and reengagement is achievable, particularly if stakeholders have been engaged in the design, conduct, and evaluation of programs.